Owning Devices for Counterfeiting Values - Bîrzu, Bogdan (Acta Universitatis Danubius. Juridica, 2022)
The paper is an analysis of the crime of possession of instruments in order to falsify values, being structured in a way that allows the identification of essential elements necessary to understand the examination both theoretically and practically. The examination includes the pre-existing conditions of the crime, the objective side, the subjective side, normative forms and modalities, legislative precedents, transitional situations, as well as an introductory part where we have discussed and highlighted the recent changes in the incriminating text and the European normative determined to amend the original indictment text. The paper is part of volume IV of a university course to be published by a recognized publishing house in the field of legal sciences in the country. Given the way it is written and the depth of the examination, we appreciate that it can be useful to the students of the profile faculties in the country, as well as to the practitioners in the field.